Pejoratives: a classification of the connoted terms - Frigerio, Aldo; Tenchini, Maria Paola (Rivista Italiana di Filosofia del Linguaggio, 2019)
Interest in slurs has partly obscured the issue of pejoratives and connoted expressions in general. However, we believe that a deeper understanding of the class the slurs belong to will have a positive impact on the study of slurs as well. In this paper, we sketch out a classification of the connoted terms, in particular, the pejorative ones. First, we analyze the balance between the descriptive and the connotative dimensions of these terms in order to find their collocation along a plausible meaning continuum. Then, we focus on the connotative component and consider the following criteria by which connoted and pejorative terms can be classified: polarity, kind of attitude, conveyed level of emotion, and vulgarity.